Gender Approach in Sports: A Qualitative Study on the Social Experiences of Female Volleyball Players - Ayça Naz Altınok; Mert Kerem Zelyurt (ümit doğan üstün, 2021)
In this study, the sports and social experiences of female volleyball players were examined in terms of gender perspective. Volleyball, which stands out as a sport specific to women in the social perception has been problematized in terms of the social experiences of female athletes. The study was conducted with a qualitative method. Semi-structured in-depth interview was used as the data collection tool and was designed according to the phenomenological pattern. Accordingly, 15 female athletes between the ages of 30-67 who had at least 10 years of volleyball sports experience between 1980-2019 were interviewed. Document analysis was used as an auxiliary data collection technique. The research findings are divided into six themes. These themes are; 'Women's volleyball in Turkish sports history, Social perception and legitimization forms of the female volleyball players body, the positioning of volleyball as a feminine sport branch, "Sultans of the net" as a local identity and representation style, Social institutions and female athlete experience: socialization forms between volleyball and household (family) and Mobbing, harassment and abuse in volleyball. As a result of the analysis of the findings, it was seen that there were differences and continuities between generations in the socialization processes of volleyball women due to gender relations. Women's volleyball in Turkey in the early stages of volleyball is encoded through the assessment specific to bodies and women's sporting performance remains in the shadow of female sexuality. Today women are more successful in the volleyball than men. This situation leads to the legitimization and coding of volleyball as a feminine sport branch through gender stereotypes. Throughout the history of Turkish sports, it is seen that different forms of representation have been attributed to volleyball women by the media. According to our research, these forms of representation are placed in social perception with the "naked calf", "Atatürk's daughters" and "Sultans of the net" discourse respectively. Today the "Sultans of the net" discourse is widely used in all social institutions in Turkey. This has led to the transformation and institutionalization of this discourse into a local and national identity represented by women volleyball players in Turkey. It is seen that the discourse is also internalized by volleyball players. Although being a volleyball player in Turkey positively affects women's social identity and status in the context of economic freedom and public visibility, it cannot free women from the hierarchy of the patriarchal structure in domestic roles. Volleyball women are often exposed to mobbing and harassment from coaches and managers.